PENERAPAN PEMBELAJARAN KOOPERATIF TGT UNTUK MENGOPTIMLKAN PEMAHAMAN HURUF KAPITAL PADA KELAS 5 SDN KARANGREJO 04 - Kamilaturrohmah; Istifani; Fajar Surya Hutama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to improve students understanding of the material on the use of capital letters by applying the Team Games Tournament (TGT) cooperative learning model in grade 5 of SDN Karangrejo 04. Initial observations showed that learning completeness was only 14%. The conventional learning method used in the pre-cycle stage is not optimal in increasing students' participation, motivation and understanding of this material. Therefore, this study implements the TGT model in two cycles using the Classroom Action Research (CAR) method which includes the planning, implementation, observation, and reflection stages. The results of the study show that the application of the TGT model can increase students understanding of the use of capital letters. The average student score increased from 52.59 in the pre-cycle to 73.33 in the first cycle and 92.59 in the second cycle. In addition, the percentage of learning completeness increased from 14% in the pre-cycle to 56% in the first cycle and reached 96% in the second cycle. Observation of students' motivation also showed an increase in aspects of enthusiasm, focus, and learning effort. Thus, the TGT learning model has proven to be effective in improving capital comprehension and building student motivation and involvement in learning.